Evaluation of Laser Irradiation Effect on the Structural and Optical Properties of Mg and MgO Nanoparticles Prepared Via Green Synthesis - Rashid, Sahar Naji (Iraqi Journal of Science, 2026)
Laser processing of materials is currently one of the most interesting topics, especially with regard to nanomaterials. In this work, magnesium and magnesium oxide nanoparticles were irradiated with laser after they were synthesized using the green method to compare their characterization without and with laser exposure using some structural and optical characterization techniques. These nanoparticles were synthesized from magnesium chloride salt and saffron plant extract and then irradiated with a diode laser with three exposure periods (30, 60, and 90 sec). The results of the analyses showed that laser irradiation caused a reduction in the average grain sizes and diameters of the synthesized nanoparticles and the regularity of the surface morphology, in addition to an increase in their absorption, and this behavior increases with increasing the period of laser irradiation.